Comparative analysis of features professional employees sensorineural hearing loss in a variety of sectors - E. E. Adeninskaya; Y. Y. Gorblyansky; O. G. Khoruzhaya (Acta Biomedica Scientifica, 2013)
The article presents comparative analysis of the results of complex long-term examination of occupational male patients of three types of economic activity: civil aviation, engineering and coal mining industry with determined diagnosis of sensorineural hearing loss.